On the relationship between labor market policies and outcomes in Bolivia: A search and matching approach - Nogales, Ricardo; Córdova, Pamela; Urquidi, Manuel (Estudios de Economía, 2019)
In this paper we assess the relationship between labor policies and market outcomes in Bolivia, accounting for a large informal sector mostly comprised of self-employed entrepreneurs. We calibrate a job search and matching model to reproduce labor market features in 2013, a period in which important labor policy changes were simultaneously active for the first time. We focus on some effects of three specific policies namely a 14th salary, minimum wage increases and contributions to a ‘solidary pension fund’ on the sorting of workers between unemployment, formal and informal employment, as well as on the formal wage schedule.